Comparison of ultrasound and Contrast- enhanced computed tomography in clinically diagnosed cases of acute pancreatitis - Jaiswal, Pooja; Shrestha, Shreejana; Dwa, Yogita (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Acute pancreatitis (AP) is an acute, mainly diffuse, inflammatory process of the pancreas with dynamic imaging characteristics and a multitude of possible complications. Imaging plays an important role in the diagnosis of AP. As most of the AP cases are gallstone-related, ultrasound (USG) is the most common initial radiologic investigation of choice. Contrast-enhanced CT (CECT) is the standard technique for overall assessment of AP and its complications. This study aims to compare diagnostic accuracy of imaging findings of USG with CECT.Method: This was a retrospective review of imaging findings of USG and CECT in clinically diagnosed cases of AP who visited Radiology Department of Patan Hospital, Patan Academy of Health Sciences, Kathmandu, Nepal during 2015 to 2019 and had undergone USG and CECT. The diagnostic accuracy of USG and CECT imaging findings were compared. Study was approved ethically.Result: Among 210 clinically diagnosed cases of acute pancreatitis, USG accurately diagnosed 97(46.2%), CECT 180(85.7%). Both the modalities detected cholelithiasis in 17% of the cases. Out of 97 cases, 85 showed focal or diffuse enlargement of pancreas on USG.Conclusion: The CECT showed higher diagnostic accuracy for acute pancreatitis as compared to ultrasound, 85.7% vs. 46.2%. The overall visualization of the imaging features of AP and its complications was better by CECT than by USG.